Setting the scene for Mediterranean litterscape management: The first basin-scale quantification and mapping of floating marine debris. (August 2020) - Lambert, C.; Authier, M.; Dorémus, G.; Laran, S.; Panigada, S.; Spitz, J.; Van Canneyt, O.; Ridoux, V.
Abstract: Plastic pollution has become one of the biggest environmental concerns of the Anthropocene as it represents a major threat to both wildlife and human health. Garbage patches in the world's oceans are well documented, but quantitative assessments of floating debris are still lacking in some major areas. The Mediterranean Sea is one such area, despite being one of the most plastic polluted environments. We used data from the first international basin-scale survey of the Mediterranean Sea to provide the first abundance estimate of floating mega-debris (>30 cm) and map their distribution over the entire Mediterranean Sea. We estimated the total number of floating mega-debris at 2.9 million items, taking into account imperfect detection. Items larger than 30 cm represent only one fourth of the complete load of anthropogenic debris (>2 cm) in the Mediterranean, which scales up the estimate to 11.5 million floating debris. The highest densities were observed in the central Mediterranean, and the lowest in the eastern basin. This acute marine pollution might threaten to disrupt entire ecosystems through its impact on marine fauna (entanglement, ingestion, contamination), eventually impacting the tourism industry and the well-being of Mediterranean populations. Graphical abstract: Image 1 Highlights: The Mediterranean Sea is the 6th garbage patch. The 2018's ACCOBAMs Survey Initiative is the first comprehensive basin-scale survey. More than 41 000 floating mega-debris were sighted by eye. Floating debris over the Mediterranean estimated to a total of 11.5 million items. Highest densities of debris observed in central basin, lowest in eastern basin. Abstract : Building from the first international basin-scale visual survey of the Mediterranean Sea, the present study provides the first estimate of the abundance of floating debris over the entire Mediterranean Sea and the first basin-scale map of mega-debris distribution.